An Overview of the Relationship between Psychological Capital and Entrepreneurial Orientation of Startup Companies - Dinh Quy, Nguyen Le (VNU Journal of Science: Policy and Management Studies; Vol 36 No 1, 2020)
Start-up is a driving force to promote technological innovation, create new jobs, and support economic growth. Throughout the ongoing progress of developing Vietnam’s economic growth model, the start-up and improving labor productivity issues have been playing an increasingly crucial part. In this study, the authors examined the relationship between psychological capital and business orientation of start-up companies to provide a model for optimal utilization of these companies’ resources. It has been observed that the intermediary role of employee’s engagement in the relationship between psychological capital and organizational commitment within the companies is genuinely crucial and that effective and systematic psychological capital intervention will provide a solid foundation for the improvement of labor productivity.